Analisis Pendapatan Petani Bawang Merah Berdasarkan Penggunaan Pupuk Organik dan Anorganik di Kecamatan Anggeraja Kabupaten Enrekang (Studi Kasus Desa Pekalobean) - nurhaedah nurhaedah; Andi Nuddin; Moh Nadir (Universitas Muslim Maros, 2023)
This research was conducted with the aim of comparing the production and income shallots farmers using organic and inorganic fertilizers on Bima shallot varieties and local shallot varieties in Pekalobean Village, Anggeraja District, Enrekang Regency. This study is a qualitative descriptive study to determine the comparison of production and income of shallot farmers using organic and inorganic fertilizers. The analysis technique used is descriptive analysis where the researcher explains the data and facts obtained during the field research stage. The results of this study indicate that based on the research conducted, it can be seen that the total income obtained by Mr. Moh. Nadir B with the Bima shallot variety using organic fertilizer was Rp 3,871,625 and the Bima shallot variety using inorganic fertilizer was Rp 3,787,225, while the local shallot variety using organic fertilizer had an income of Rp 2,264,625 and the local shallot variety using inorganic fertilizer had an income of Rp 3,162,625. The use of inorganic fertilizers resulted in higher shallot production compared to the use of organic fertilizers.